Korelasi status gizi dengan kebugaran calon atlit olahraga sepeda (Talent scouting) - Muhammad Yani; Azhari Azhari; Teuku Muhammad Ilzana; Farid Bastian (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2022)
The talent scouting process is fundamental in improving the performance of bicycle athletes. The selection process still focuses on prospective athletes' nutritional and fitness factors. The Indonesian Bicycle Sports Association of Banda Aceh City selects prospective bicycle sports athletes from an early age (adolescence) to be fostered in sustainability. The study measures the correlation between nutritional status (BMI) and fitness (standing board jump, vertical jump, and 30-meter sprint) in prospective bicycle sports athletes. The research design is Cross-sectional and has been carried out at the Indonesian Bicycle Sports Association (ISSI) Banda Aceh City 2021. Subjects of as many as 180 prospective athletes were taken by purposive random. Measuring nutritional status was measured by assessing BMI, while fitness was measured by standing board jump, vertical jump, and 30-meter sprint. Statistical analysis using Linear Regression test at CI: 95%. The results showed that there was a correlation between BMI and standing board jump (p= 0,000), BMI with a vertical jump (p= 0,004), and BMI with a 30-meter sprint (p = 0.000) in prospective bicycle athletes in Banda Aceh City. In conclusion, nutritional status (BMI) correlates with fitness (standing board jump, vertical jump and 30-meter sprint) in prospective bicycle athletes in Banda Aceh City.